Friction pair
By adding a specific proportion of carbonaceous lubricating material and an inorganic friction adjustment material with a Mohs hardness of more than 6 to the friction material without copper components, the thermal conductivity of the friction material is adjusted, and the problem of thermal decomposition of organic matter at high temperatures is solved, and the braking performance stability and wear resistance of the friction material are improved.
Patent Information
- Application Number
- CN202180042863.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-06-16
- Filing Date
- 2021-06-09
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-06-09
AI Technical Summary
The existing friction materials without copper components thermally decompose organic matter at high temperatures, resulting in a decrease in braking performance stability, and the thermal decomposition of the adhesive material reduces the wear resistance of the friction materials.
The friction material composition without copper components and iron metal fibers is used, which contains a bonding material, a fiber base material and a friction adjustment material. By adding 10 to 15% by weight of carbonaceous lubricating material and 15 to 30% by weight of inorganic friction adjustment material with a Mohs hardness of 6 or more, the thermal conductivity of the friction material is within the range of 1.2 to 3.0W/m·K.
The braking performance stability and wear resistance of friction materials are improved, the thermal decomposition of organic matter is inhibited, and the performance of friction materials is improved through the lubrication effect of carbonaceous lubricating materials.
Smart Images

Figure BDA0004000116800000101 
Figure BDA0004000116800000111 
Figure BDA0004000116800000121
Abstract
Description
Technical Field
[0001] The invention relates to a friction pair, in particular to a friction pair used for vehicles such as passenger cars. Background Art
[0002] Conventionally, as a friction member of a disc brake for a passenger car, a disc brake pad is used, in which a friction material is bonded to a metal base member.
[0003] In recent years, due to the demand for quiet braking, disc brake pads using a friction material called NAO material that generates less braking noise have become widely used.
[0004] The friction material of NAO material is formed by molding a friction material composition containing a binder, a fiber base material other than steel fibers such as steel fibers and / or stainless steel fibers, and a friction adjustment material. It is a friction material classified in parallel with semi-metallic friction materials and / or low-steel friction materials containing steel fibers as fiber base materials. In addition, in recent years, there are also legal regulations on the content of copper components in the United States, and friction materials containing only 5% by weight or less copper or no copper at all are generally developed.
[0005] Patent document 1 describes a friction material composition and a friction material obtained by molding the friction material composition. The friction material composition contains a fiber substrate, a friction adjusting material and a bonding material. The content of copper in the friction material composition is 0.5% by mass or less in terms of copper element. The friction adjusting material contains granular titanate obtained by granulating titanate, and the average particle size of the granular titanate is 100 to 250 μm.
[0006] Patent document 2 describes a friction material composition, which is a friction material containing a fiber base material, an inorganic filler, an organic filler and a binder, and a copper content of 0.5 mass % or less. As the inorganic filler, it contains an abrasive with an average particle size of 3 to 5 μm and an abrasive with an average particle size of 9 to 13 μm. At the same time, as the inorganic filler, it contains titanate with an average particle size of 1.5 to 4.5 μm and titanate with an average particle size of 15 to 45 μm.
[0007] As a counter-friction material for a disc brake pad having such a friction material containing almost no copper components, a cast iron disc rotor as described in Patent Document 3 is used. Such a cast iron disc rotor has low corrosion resistance and has the problem of rusting during use, so a solution is needed in the friction material.
[0008] For example, Patent Document 4 discloses a friction material comprising a bonding material, a friction adjusting material and a fiber substrate, which has improved rust removal properties on the abrasive material by not containing a copper component but containing 10 to 20 volume % of at least one titanate compound having a plurality of protrusions and 1 to 20 volume % of biosoluble inorganic fibers.
[0009] However, as the installation of regenerative brakes is promoted due to the popularization of electric vehicles and hybrid vehicles, the braking load of the friction material of the conventional hydraulic brake is reduced, so even if the technology of Patent Document 4 is used, there is a problem that sufficient rust removal performance cannot be obtained.
[0010] Therefore, disc rotors made of stainless steel having excellent rust resistance are increasingly being used.
[0011] Patent Document 5 discloses a four-wheel disc rotor made of a stainless steel plate having a martensitic structure or a mixed structure of a martensitic phase and a ferrite phase.
[0012] Patent Document 6 describes a disc rotor for an automobile having a structure containing martensite and carbonitride and optionally containing ferrite.
[0013] Patent Document 7 describes a disc rotor for an automobile made of a stainless steel plate, wherein the stainless steel plate is characterized by containing, by mass%, C: 0.005-0.100%, Si: 0.01-1.00%, Mn: 0.010-3.00%, P: 0.040% or less, S: 0.0100% or less, Cr: 10.0-14.0%, N: 0.005-0.100%, V: 0.03-0.30%, Al: 0.001-0.050%, B: 0.0002-0.0050%, Ni: 0-2.00%, Cu: 0-2.00%, Mo: 0~1.00%, W: 0~1.00%, Ti: 0~0.40%, Nb: 0~0.40%, Zr: 0~0.40%, Co: 0~0.400%, Sn: 0~0.40%, REM: 0~0.050% or less, Mg: 0~0.0100%, Ca: 0~0.0100%, Sb: 0~0.50%, Ta: 0~0.3000%, Hf: 0~0.3000%, Ga: 0~0.1000%, the remainder is composed of Fe and impurities, the metal structure is composed of ferrite phase, and 10~50 / 100μm are used in any cross section. 2 Carbonitrides having a circle-equivalent diameter of 0.3 μm or more are present.
[0014] In this context, there is a need for a friction material made of a friction material composition that does not contain copper components, which is suitable for stainless steel disc rotors with excellent rust resistance. However, it is clear that when the friction material reaches a high temperature, organic matter such as a bonding material and an organic friction adjustment material contained in the friction material is easily thermally decomposed, and the decomposed organic matter is trapped in the friction surface, resulting in a decrease in the stability of the braking performance. In addition, the thermal decomposition of the bonding material causes a significant decrease in the strength of the friction material, thereby reducing the wear resistance of the friction material.
[0015] Prior art literature
[0016] Patent Literature
[0017] Patent Document 1: Japanese Patent Application Publication No. 2017-57312
[0018] Patent Document 2: Japanese Patent Application Publication No. 2018-162385
[0019] Patent Document 3: Japanese Patent Application Laid-Open No. 2-134425
[0020] Patent Document 4: Japanese Patent Application Publication No. 2017-149971
[0021] Patent Document 5: Japanese Patent Application Publication No. 2016-117925
[0022] Patent Document 6: Japanese Patent Application Publication No. 2019-173086
[0023] Patent Document 7: Japanese Patent Application Publication No. 2019-178419 Summary of the invention
[0024] Problems to be solved by the invention
[0025] The object of the present invention is to provide a friction pair having excellent braking performance stability and anti-wear property of the friction material, the friction pair comprising a disc brake pad having a friction material composed of a friction material composition, and a disc rotor made of stainless steel, the friction material composition containing a binder, a fiber substrate, a friction adjusting material, and not containing a copper component and an iron-based metal fiber.
[0026] Means used to solve problems
[0027] As a result of intensive research by the inventors of the present invention, a friction pair was discovered, comprising a disc brake pad having a friction material composed of a friction material composition, and a disc rotor made of stainless steel, wherein the friction material composition contains a bonding material, a fiber substrate, a friction adjustment material, and does not contain a copper component and iron-based metal fibers, and the friction material composition does not contain metal fibers other than iron-based metal fibers. By using a friction material composition containing a specific amount of a carbonaceous lubricating material as a friction adjustment material and a specific amount of an inorganic friction adjustment material with a Mohs hardness of 6 or more, and setting the thermal conductivity of the friction material within a specific range, a friction pair having excellent braking performance stability and wear resistance of the friction material can be obtained, thereby completing the present invention.
[0028] The present invention relates to a friction pair, which includes a disc brake pad having a friction material composed of a friction material composition, and a disc rotor made of stainless steel. The friction material composition contains a bonding material, a fiber substrate, and a friction adjusting material, and does not contain a copper component and an iron-based metal fiber. The present invention is based on the following technology.
[0029] (1) A friction pair comprising a disc brake pad having a friction material composed of a friction material composition, and a disc rotor made of stainless steel, wherein the friction material composition contains a binder, a fiber base material, and a friction adjusting material, and does not contain a copper component and iron-based metal fibers, characterized in that the friction material composition does not contain metal fibers other than iron-based metal fibers, and contains 10 to 15% by weight of a carbonaceous lubricating material as the friction adjusting material, and 15 to 30% by weight of an inorganic friction adjusting material having a Mohs hardness of 6 or more, based on the total amount of the friction material composition, and the thermal conductivity of the friction material is 1.2 to 3.0 W / m·K.
[0030] (2) The friction pair according to (1), wherein the carbonaceous lubricating material is one or more selected from artificial graphite, natural graphite, graphite flake powder, petroleum coke, coal coke, elastic graphitized carbon, and oxidized polyacrylonitrile fiber powder.
[0031] (3) The friction pair according to (2), wherein the carbonaceous lubricating material comprises graphite flake powder, petroleum coke, and elastic graphitized carbon.
[0032] (4) The friction pair according to any one of (1) to (3), wherein the inorganic friction modifier having a Mohs hardness of 6 or more contains 13 to 28% by weight of zirconium oxide having an average particle size of 0.5 to 8.0 μm relative to the total amount of the friction material composition.
[0033] Effects of the Invention
[0034] According to the present invention, a friction pair can be provided, which has excellent braking performance stability and wear resistance of the friction material, and includes a disc brake pad having a friction material composed of a friction material composition, and a disc rotor made of stainless steel, wherein the friction material composition contains a binder, a fiber substrate, and a friction adjusting material, and does not contain a copper component and an iron-based metal fiber. DETAILED DESCRIPTION
[0035] Compared with cast iron disc rotors, stainless steel disc rotors have lower thermal conductivity and thermal diffusivity, and compared with cast iron, stainless steel has a slightly higher specific gravity but slightly higher strength. Therefore, assuming that the stainless steel disc rotor has the same weight and strength as the cast iron disc rotor, the thickness of the disc rotor will be designed to be thinner. As a result, the heat capacity of the disc rotor becomes smaller, the disc rotor is more likely to store heat, and the temperature of the friction material is more likely to reach a high temperature.
[0036] When the friction material reaches a high temperature, the organic matter such as the adhesive material and the organic friction adjustment material contained in the friction material is easy to be thermally decomposed, and the decomposed organic matter is trapped in the friction surface, resulting in a decrease in the stability of the braking performance. In addition, the thermal decomposition of the adhesive material significantly reduces the strength of the friction material, thereby reducing the wear resistance of the friction material.
[0037] Therefore, the present invention relates to a friction pair, comprising a disc brake pad having a friction material composed of a friction material composition and a disc rotor made of stainless steel, wherein the friction material composition contains a binder, a fiber base material, a friction adjusting material, and does not contain a copper component and iron-based metal fibers, and uses a friction material composition that does not contain metal fibers other than iron-based metal fibers, and contains 10 to 15% by weight of a carbonaceous lubricating material as a friction adjusting material relative to the total amount of the friction material composition, and 15 to 30% by weight of an inorganic friction adjusting material with a Mohs hardness of 6 or more relative to the total amount of the friction material composition, and the thermal conductivity of the friction material is 1.2 to 3.0 W / m·K.
[0038] Heat dissipation properties can be imparted to the friction material by adding a relatively large amount of a carbonaceous lubricant as a friction modifier relative to the total amount of the friction material composition and setting the thermal conductivity of the friction material within a specific range.
[0039] In this specification, the thermal conductivity of the friction material is a value obtained by cutting out a friction material portion from a disc brake pad as a final product and measuring it by a hot wire method based on rapid thermal conductivity measurement.
[0040] By setting the content of the carbonaceous lubricant and the thermal conductivity of the friction material within the above range, the heat dissipation of the friction material can be improved and the temperature rise of the friction material can be suppressed. As a result, the thermal decomposition of organic matter contained in the friction material is suppressed, and the wear resistance is improved by the lubricating effect of the carbonaceous lubricant.
[0041] However, due to the lubricating effect of the carbonaceous lubricating material, simply adding a relatively large amount of the carbonaceous lubricating material will reduce the stability of the braking performance. Therefore, in order to offset the lubricating effect caused by the addition of the carbonaceous lubricating material, an inorganic friction modifier having a Mohs hardness of 6 or more is added as a friction modifier in an amount of 15 to 30% by weight relative to the total amount of the friction material composition.
[0042] By setting the content of the inorganic friction modifier having a Mohs hardness of 6 or more in the friction material composition within the above range, a grinding effect on the disc rotor can be obtained, and excellent braking performance stability can be obtained when a relatively large amount of carbonaceous lubricating material is added.
[0043] In the present invention, regarding the Mohs hardness, the old Mohs hardness represented by “1. talc, 2. gypsum, 3. calcite, 4. fluorite, 5. apatite, 6. orthoclase, 7. crystal, 8. topaz, 9. corundum, 10. diamond” is applied.
[0044] As carbonaceous lubricating materials, one or more selected from artificial graphite, natural graphite, graphite flake powder, petroleum coke, coal coke, elastic graphitized carbon, and oxidized polyacrylonitrile fiber powder can be used in combination. It is particularly preferred to use a combination of graphite flake powder, petroleum coke, and elastic graphitized carbon.
[0045] Graphite flake powder is a raw material obtained by thermally expanding natural graphite after acid treatment, forming the obtained expanded graphite into flakes by roller pressing, and then crushing the graphite flakes. Elastic graphitized carbon is a raw material obtained by graphitizing a carbonaceous raw material at 1900℃ to 2700℃ until the degree of graphitization stops at 80 to 95%.
[0046] As an inorganic friction adjusting material with a Mohs hardness of 6 or above, one selected from ferrosoferric oxide, magnesium oxide, zirconium oxide, silicon dioxide, zirconium silicate, γ-alumina, α-alumina, silicon carbide, glass fiber, biosoluble ceramic fiber, rock wool, basalt fiber, etc. can be used alone or in combination of two or more.
[0047] As part of the inorganic friction modifier having a Mohs hardness of 6 or more, which is added at 15 to 30% by weight relative to the total amount of the friction material composition, zirconium oxide having an average particle size of 0.5 to 8 μm is preferably added, and its content is preferably 13 to 28% by weight relative to the total amount of the friction material composition.
[0048] In this specification, the average particle size is a value of a 50% particle size measured by a laser diffraction particle size distribution measurement method.
[0049] <Friction material composition>
[0050] The friction material used in the friction pair of the present invention is composed of a friction material composition, which contains, in addition to the above-mentioned carbonaceous lubricating material and the above-mentioned inorganic friction adjusting material with a Mohs hardness of 6 or more, a binder, a fiber base material and a friction adjusting material commonly used in friction materials.
[0051] As the binding material, there can be listed straight-chain phenolic resin, acrylic rubber modified phenolic resin, silicone rubber modified phenolic resin, nitrile rubber modified phenolic resin, cashew nut oil modified phenolic resin, aralkyl modified phenolic resin (phenol aralkyl resin) obtained by reacting phenols, aralkyl ethers and aldehydes, acrylic rubber dispersed phenolic resin, silicone rubber dispersed phenolic resin, fluoropolymer dispersed phenolic resin and other binding materials commonly used in friction materials. They can be used alone or in combination of two or more.
[0052] The content of the binder is preferably 4 to 9 wt %, more preferably 6 to 8 wt %, based on the total amount of the friction material composition.
[0053] Examples of the fiber substrate include organic fibers commonly used in friction materials, such as aramid fibers, acrylic fibers, cellulose fibers, and polyparaphenylenebenzobisoxazole fibers. These fibers may be used alone or in combination of two or more.
[0054] The content of the fiber base material is preferably 1 to 5% by weight, more preferably 2 to 4% by weight, based on the total amount of the friction material composition.
[0055] As the friction adjusting material, a lubricating material, an inorganic friction adjusting material, and an organic friction adjusting material can be used.
[0056] As lubricants, in addition to the above-mentioned carbonaceous lubricants, metal sulfide lubricants such as tin sulfide, molybdenum disulfide, iron sulfide, bismuth sulfide, zinc sulfide, and composite metal sulfides can also be listed. These can be used alone or in combination of two or more.
[0057] The total content of the lubricating material and the carbonaceous lubricating material is preferably 10 to 18 wt %, more preferably 11 to 16 wt %, based on the total amount of the friction material composition.
[0058] As inorganic friction adjusting materials, in addition to inorganic friction adjusting materials with a Mohs hardness of 6 or more, calcium hydroxide, calcium carbonate, barium sulfate, talc, dolomite, zeolite, calcium silicate hydrate, columnar titanate, plate-like titanate, granular titanate, flaky titanate, titanate with an amorphous shape having multiple protrusions (titanates include potassium titanate, potassium lithium titanate, potassium magnesium titanate, sodium titanate, etc.), wollastonite, sepiolite, etc. can also be listed. They can be used alone or in combination of two or more.
[0059] The total content of the inorganic friction modifier and the inorganic friction modifier having a Mohs hardness of 6 or more is preferably 60 to 82 wt %, more preferably 65 to 76 wt %, based on the total amount of the friction material composition.
[0060] As organic friction adjusting materials, there can be listed cashew nut oil friction powder, tire tread rubber powder, polytetrafluoroethylene powder, or vulcanized rubber powder or unvulcanized rubber powder such as acrylic rubber, isoprene rubber, nitrile rubber, styrene-butadiene rubber, butyl rubber, silicone rubber, etc., which are organic friction adjusting materials commonly used in friction materials. They can be used alone or in combination of two or more.
[0061] The content of the organic friction adjusting material is preferably 3 to 8% by weight, more preferably 5 to 7% by weight, based on the total amount of the friction material composition.
[0062] <Method for manufacturing disc brake pad>
[0063] The disc brake pad according to the present invention is generally manufactured by the following process:
[0064] A mixing process of uniformly mixing the friction material composition (friction material raw material) prepared in a predetermined amount using a mixer to obtain a friction material raw material mixture,
[0065] The obtained friction material raw material mixture is superimposed on a back plate which has been cleaned, surface treated and coated with an adhesive material in advance, and then placed in a thermoforming mold for heat and pressure molding.
[0066] The obtained molded product is heated to complete the heat treatment process of the curing reaction of the adhesive material.
[0067] A coating process that uses spraying or electrostatic powder coating to apply the paint.
[0068] The coating baking process of the baking paint, and
[0069] A grinding process that uses a rotating grindstone to form a friction surface.
[0070] After the heating and pressurizing step, the coating step, the heat treatment step also serving as the coating baking step, and the polishing step may be sequentially performed for production.
[0071] If necessary, before the heating and pressing process, the following can be carried out:
[0072] The granulation process of granulating the friction material raw material mixture,
[0073] The kneading process of kneading the friction material raw material mixture,
[0074] A preforming step of placing the friction material raw material mixture or the granulated product obtained in the granulating step and the kneaded product obtained in the kneading step into a preforming die to form a preform,
[0075] The scorching step may be performed after the heating and pressure molding step.
[0076] <Stainless steel disc rotor>
[0077] As the stainless steel disk rotor, for example, a disk rotor made of martensitic stainless steel or ferritic stainless steel can be used.
[0078] Example
[0079] The present invention will be specifically described below with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples.
[0080] [Methods for producing friction materials of Examples 1 to 14 and Comparative Examples 1 to 5]
[0081] The friction material compositions having the compositions shown in Table 1 and Table 2 were placed in Mix in a mixer for 5 minutes to obtain a friction material composition mixture. Pressurize the friction material composition mixture at 30 MPa for 10 seconds in a molding mold to obtain a friction material preform. Place the friction material preform on a steel back plate that has been pre-cleaned, surface-treated, and coated with an adhesive, and mold it in a hot molding mold at a molding temperature of 150°C and a molding pressure of 40 MPa for 10 minutes to obtain a friction material mold. After heat treating (post-curing) the friction material mold at 200°C for 5 hours, grind it to form a friction surface and produce a disc brake pad for a passenger car.
[0082] Table 1
[0083]
[0084] Table 2
[0085]
[0086] Furthermore, the friction material of the disc brake pad was cut into a size of 25 mm×15 mm×15 mm to obtain test pieces of Examples 1 to 14 and Comparative Examples 1 to 5.
[0087] Table 3 shows the "test conditions", "material of the friction material", "evaluation items" and "evaluation criteria" used when these test pieces were used to detect the stability of the braking performance and the wear resistance of the friction material.
[0088] Table 3
[0089]
[0090] The "evaluation items" and "evaluation criteria" of the "product appearance" of these test pieces are shown in Table 4. The "product" referred to here is the final product "disc brake pad".
[0091] Table 4
[0092]
[0093] Tables 5 and 6 show the evaluation results of “braking performance stability”, “wear resistance of friction material” and “product appearance” shown in Tables 3 and 4, which were performed for each Example and each Comparative Example.
[0094] Table 5
[0095]
[0096] Table 6
[0097]
[0098] It can be seen from Table 5 and Table 6 that the friction material meeting the conditions of the present invention is good in terms of braking performance stability, friction material wear resistance and product appearance.
[0099] Industrial Applicability
[0100] According to the present invention, a friction pair can be provided, which has excellent braking performance stability, friction material wear resistance and product appearance. The friction pair includes a disc brake pad having a friction material composed of a friction material composition, and a stainless steel disc rotor. The friction material composition contains a bonding material, a fiber substrate, and a friction adjustment material, and does not contain copper components and iron-based metal fibers. The friction pair has extremely high practical value.
Claims
1. A friction pair comprising a disc brake pad having a friction material composed of a friction material composition, and a disc rotor made of stainless steel, wherein the friction material composition contains a binder, a fiber substrate, a friction adjusting material, and does not contain a copper component and an iron-based metal fiber, characterized in that: The friction material composition does not contain any metal fiber other than the iron-based metal fiber, and contains 11 to 13 wt % of a carbonaceous lubricating material including graphite flake powder, petroleum coke and elastic graphitized carbon as the friction adjusting material, and 15 to 30 wt % of an inorganic friction adjusting material having a Mohs hardness of 6 or more, relative to the total amount of the friction material composition, wherein 20 to 25 wt % of zirconium oxide having an average particle size of 0.5 to 8.0 μm is contained as a part of the inorganic friction adjusting material having a Mohs hardness of 6 or more, relative to the total amount of the friction material composition, and the thermal conductivity of the friction material is 1.6 to 2.3 W / m·K.
Citation Information
Patent Citations
Disk rotor material
JP1990134425A
Four wheel stainless steel disk brake rotor and method for manufacturing the same
JP2016117925A
Friction material composition and friction material
JP2017057312A
Friction material
JP2017149971A
Friction material composition, and friction material and friction member using the friction material composition
JP2018162385A